Norges Bank's Endogenous Interest Rate Path and Its Impact on Interest Rate Expectations - Olav Syrstad; Dagfinn Rime (Norges Bank, 2014)
Norges Bank has published its own forecasts for the key policy rate since 2005. The Reserve Bank of New Zealand introduced this practice as early as in 1997. Later, in 2007, the Swedish Riksbank also started to publish its interest rate forecasts, followed by the Czech National Bank in 2009. In this note we take a closer look at Norges Bank's interest rate forecasts and their impact on interest rate expectations extracted from market prices. Rather than attempting to answer normative questions about the desirability of interest rate forecasts, we present a short, descriptive overview of how interest rate expectations have changed around the time of publication of Norges Bank's interest rate paths. Finally, we perform a straightforward comparison of Norges Bank's and market participants' forecast accuracy.
hdl:11250/2506912
Keywords: 330